Comments on the snake-eel genus Xyrias (Anguilliformes: Ophichthidae) with the description of a new species - Mccosker, John E.; Chen, Wei-Li; Chen, Hong-Ming (Zootaxa, 2009)
Comments on the snake-eel genus Xyrias (Anguilliformes: Ophichthidae) with the description of a new species. Xyrias chioui, a new robust snake-eel species, subfamily Ophichthinae, is described on the basis of a specimen caught at 60–70 m depth on a benthic longline off Changbin, Taitung County, eastern Taiwan. It is distinguished from its congeners by having fewer vertebrae (126), 3 postorbital cephalic pores, and biserial rather than multiserial mandibular dentition. A key to the species of Xyrias is provided. Additional records of X. revulsus from the Arafura Sea and off New South Wales, Australia, extend its depth range from a few to 300 meters. The generic diagnosis of Xyrias is expanded such that the maxillary dentition ranges from a biserial to a multiserial condition.